Rewritings/refoldings/refleshings: fictive publics and the material gesture of defamiliarization. Issue 5 (2nd September 2016) - Palmer, Helen
Abstract: This paper develops the concept of fictive publics through the proximate gestures of rewriting, refolding and refleshing of certain characters. Feminist and queer rewritings of canonical literary texts have become a fairly lucrative area of publication, from Angela Carter's now classic fairy tale collection The Bloody Chamber (1979) to Kathy Acker's Eurydice in the Underworld (1997), and a more recent spate of mythological rewritings including Ali Smith's Girl Meets Boy (2007) and Ursula K. Le Guin's Lavinia (2008). The intervention into patriarchal mythical structures via rewriting has been well documented, but the ways in which this interrelates with the philosophical feminist and new materialist projects of the radical rewriting of modernity itself has not yet been investigated. In this paper, I argue that a paradoxical relationality structures the concept of fictive publics, which is analogous to the modernist gesture of defamiliarization. Publics presuppose a proximity of strangers, and the concept of proximity is vital to queer studies. Rewriting is constituted by a particular type of radical and contentious movement which has significance for feminist thought. Using these examples, I explore the creative process of radical rewriting as a material gesture of intervention.